Kualitas Pendidikan di Sulawesi Barat - Swajir, Nadila Swajir (Universitas Negeri Makassar, 2023)
Abstract. This study contains information on the quality of education in the West Sulawesi Province of Indonesia. Understanding of education, intent and purpose of knowing the quality of education in West Sulawesi and the solution to overcome the low quality of education in West Sulawesi. Education is human capital which is very important for a nation. With quality education humans can acquire knowledge such as ethics and morals, and various skills. However, the quality of education in West Sulawesi is still relatively low when compared to several regions in Indonesia, even in some countries. This can be seen by the 2021 data from BPS and the Ministry of National Education. Based on the 2022 Human Development Index data the quality of education in West Sulawesi is ranked 31st. To overcome this problem the government seeks to improve the quality of education through increasing education budgets by improving educational facilities and increasing access to education that is fair and equitable.Abstrak. Penelitian ini memuat tentang bagaimana kualitas pendidikan di Provinsi Sulawesi Barat Indonesia. Pengertian pendidikan, maksud dan tujuan mengetahui kualitas pendidikan di Sulawesi Barat serta solusi mengatasi rendahnya kualitas pendidikan di Sulawesi Barat. Pendidikan merupakan modal manusia (human capital) yang sangat penting bagi sebuah bangsa. Dengan pendidikan berkualitas manusia dapat memperoleh pengetahuan seperti etika dan moral, dan berbagai keahlian. Akan tetapi kualitas pendidikan di Sulawesi Barat saat ini masih tergolong rendah apabila dibandingkan dengan beberapa daerah di Indonesia, bahkan di beberapa negara. Hal tersebut bisa dilihat dengan adanya data dari BPS dan Depdiknas tahun 2021. Berdasarkan data Indeks Pembangunan Manusia tahun 2022 kualitas pendidikan Sulawesi Barat berada pada peringkat ke 31. Untuk mengatasi masalah tersebut pemerintah berupaya meningkatkan kualitas pendidikan melalui peningkatan anggaran pendidikan dengan memperbaiki sarana dan prasarana pendidikan, serta peningkatan akses pendidikan yang adil dan merata.